Philo - Philo Alexandrinus (Loeb classical library, 1929)
The philosopher Philo was born about 20 BCE to a prominent Jewish family in Alexandria, the chief home of the Jewish Diaspora as well as the chief center of Hellenistic culture; he was trained in Greek as well as Jewish learning. In attempting to reconcile biblical teachings with Greek philosophy he developed ideas that had wide influence on Christian and Jewish religious thought.